2005
DOI: 10.1128/iai.73.7.4098-4105.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the nfa1 Gene Cloned from Pathogenic Naegleria fowleri in Nonpathogenic N. gruberi Enhances Cytotoxicity against CHO Target Cells In Vitro

Abstract: The pathogenic amoeba Naegleria fowleri has a 360-bp nfa1 gene that encodes the Nfa1 protein (13.1 kDa), which is located in the pseudopodia of the amoeba, and an anti-Nfa1 antibody reduces N. fowleri-induced mammalian-cell cytotoxicity in vitro. In contrast, an anti-Nfa1 antibody cannot detect Nfa1 protein expression in the nonpathogenic amoeba Naegleria gruberi, which also possesses the nfa1 gene. In the present study, the nfa1 gene cloned from pathogenic N. fowleri was transfected into nonpathogenic N. grub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The contact‐independent mechanism involves secretory molecules, such as serine protease, phospholipase A, neuraminidase and cysteine protease . In contrast, the contact‐dependent mechanism is associated with phagocytic food‐cup structures or amoebastomes activated by Nfa1 protein, heat‐shock protein 70 and Nf‐actin protein …”
Section: Introductionmentioning
confidence: 99%
“…The contact‐independent mechanism involves secretory molecules, such as serine protease, phospholipase A, neuraminidase and cysteine protease . In contrast, the contact‐dependent mechanism is associated with phagocytic food‐cup structures or amoebastomes activated by Nfa1 protein, heat‐shock protein 70 and Nf‐actin protein …”
Section: Introductionmentioning
confidence: 99%
“…Bacteria were routinely cultured in Luria-Bertini (LB) medium at 37℃ overnight as previously described [7]. Chinese hamster ovary (CHO) cells were used for A. castellanii adhesion and in vitro cytotoxicity assay [8]. Briefly, CHO cells were cultured as a monolayer in Earle's minimal essential medium (EMEM; Gibco BRL, Grand Island, New York, USA) at 37℃.…”
mentioning
confidence: 99%
“…It is reasonable to propose that Siriraj strain, which was isolated from a patient, secreted some biological substances to the cell surface of the infected cells (Fulford and Marciano-Cabral 1986;Yum et al 2002). Previous studies reported that N. fowleri produced Nfa1 protein as the contact mechanism on the cell surface of Chinese Hamster Ovary target cells in coculture (Jeong et al 2005). In addition, cytosolic heat shock protein 70 was a new finding for heat tolerance and may relate to virulence of the amoebae (Song et al 2007).…”
Section: Days Post-inoculation Total Viable Cells ( X 10 3)mentioning
confidence: 98%
“…Vero cells have also been reported as a suitable model for evaluating the cytopathogenicity of N. fowleri (John and John 1994a, b) even though the cells had been isolated from monkey kidney. Moreover, the CHO target cell (Chinese Hamster ovary cells) has also used for testing the cytotoxicity of the amoebae and the results demonstrated that the amoebae produced the Nfa1 protein during cytopathogenesis (Jeong et al 2005). However, the suitable gold standard model representing human neuron has not yet been found.…”
Section: Introductionmentioning
confidence: 98%